A combined X-ray and neutron-powder diffraction study of a superstructure derived from Tl0.75Sr1.8Ba0.2CuOy - Jones, M; Gameson, I; Edwards, P; Michel, C; Hervieu, M; Raveau, B (2000)
We have observed a superstructure derived from the compound Tl0.75Sr1.8Ba0.2CuO(y). This compound arises from the 'collapse' of the parent oxynitrate compound TlSr2Ba2Cu2O7 (NO3) under controlled thermal decomposition. A combined X-ray and neutron powder diffraction study of the title compound indicates that the superstructure possesses the Pmmm space group, with unit cell parameters (derived from neutron diffraction data) of a = 3.7362(3) Å, b = 11.5449(9) Å, and c = 9.1494(8) Å. This superstructure takes the form of a three-fold repeat along the crystal b-axis produced through local distortions of the thallium and barium/strontium positions. This compound is nonsuperconducting due to the presence of a large number of vacancies in the electronically active copper-oxygen planes. (C) 2000 academic Press.